OPPORTUNITIES AND CHALLENGES FOR MICRO, SMALL & MEDIUM ENTERPRISES (MSMES) IN INDIA: A DETAILED STUDY - Saini, Amit Kumar; Maurya, Ajeet Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Purpose: The purpose of the study is to review the existing opportunities and challenges of MSMEs in India mainly after implementation of GST. MSMEs make up more than 90% of all enterprises in most economies, are the main drivers of job growth, and contribute significantly to both industrial output and exports. MSMEs are essential to the broader industrial growth in India as well. When compared to the industrial sector as a whole, the MSME sector has had more expansion in recent years. Since then, 50% of MSMEs in India are owned by poor communities, it is possible to assess the significance of the MSME sector. MSMEs have contributed praiseworthy role in the conversion of the economy of India is rural economy to an industrialised one. The second largest employer in India is the MSME sector, right behind the agricultural sector. They are extensively spread out around the nation and generate a wide variety of goods and services to satisfy the demands of local, national, and multinational supply chain as well as local and worldwide marketplaces. To grow this industry and increase its competitiveness, the government has offered a number of plans and initiatives. Nevertheless, this industry has been contributing a large portion in India's economy but there are numerous obstacles that make the running of this sector incredibly challenging. The current study makes an effort to pinpoint key opportunities and restrictions for MSMEs in India. Design/Methodology/Approach: The study mainly includes the review of secondary data collected from various authors, journals, magazines, government’s websites and other various unpublished sources. Findings: The study makes an effort to draw attention to the different government initiatives created to support the MSME sector in India. The study showed that while the government is making every effort to support MSMEs through a variety of measures, there are still many restrictions and challenges that this industry must overcome. Future Scope of Research: As we all know, the Indian economy is still in its early stages, and the implementation of GST in India is only five years old. Therefore, there are many sectors and areas in the Indian economy that are not fully developed, and the development of these sectors in the near future will create more opportunities and challenges for MSMEs.